Comparing The Loyalty Of Two Mini Markets’ Customers: The Role Of Store Image And Satisfaction - Usep Suhud; Mahasta Patricia Divyna (Universitas Diponegoro, 2019)
Indomaret and Alfamart are two franchise-local-mini markets in Indonesia. Side by side, they invade dwelling areas within cities: where there is an Indomaret store, there will be Alfamart, but with a lack of differentiation among them. This study aims to assess and compare the impact of store image on customer satisfaction and loyalty between two franchise-retail stores in Jakarta, Indonesia: Indomaret and Alfamart. There were 200 participants involved those who were regularly visiting one or both mini markets. Different cases showed different results. In the case of Indomaret, store image had a significant impact on customer satisfaction and loyalty, and satisfaction had a significant effect on customer loyalty. In the case of Alfamart, store image had a significant impact on satisfaction. In addition, satisfaction had a significant impact on loyalty, whereas store image had an insignificant effect on loyalty. Recommendations for management and future study are discussed.